The Relationship Between Parental Play Beliefs, Preschoolers’ Home Experience, and Executive Functions: An Exploratory Study in Ethiopia - Metaferia, Biruk K.; Takacs, Zsofia K.; Futo, Judit (Frontiers in Psychology, 2020)
Although research has highlighted the importance of home experience and especially of play in early brain development, the value of this factor for executive function (EF) development has not received the attention it deserves. The purpose of the present study was to investigate the link between parental play beliefs and preschoolers’ play frequency at home on the one hand and their EF skills on the other. Additionally, other types of home activities were also assessed. A total of 102 preschoolers (45 girls; mean age = 62.08 months; SD = 7.66 months; range: 50 - 74 months) with their parents (mean age = 35.21 years; SD = 6.96 years) representing low to middle SES families in Ethiopia participated in the study. Results revealed that children’s home activities (frequency of breakfast at home, spending mealtime together with family, participation in peer play, participation in pretend play, and participation in arts and crafts) and parental play support were significantly positively correlated with their performance on EF tasks. Hierarchical regression analyses controlling for age and SES showed that parental play support and frequency of breakfast at home were medium-sized predictors (β = .36, p < .001 and β = .31, p = .001, respectively) explaining a significant level of variance in inhibitory control, while participation in arts and crafts at home was a significant predictor (β =.22, p = .03) of children’s performance on a visual-spatial working memory task. In conclusion, parental play support and preschoolers’ home activities are important factors linked with EF development in early childhood.